Natural daylight and the simulation of its effects upon stomata - Hughes, Jonathan E. (1983)
The spectral composition of natural daylight was examined using horizontal planar receptor surfaces. During the day, incident spectra were remarkably uniform. Particular attention was paid to physiologically important variables. The mean 660:730 nm photon fluence ratio (R:FR) was 1.15, corresponding to a phytochrome photoequilibrium of 0.53, but in late winter R:FR was lower than in late summer (ca. 1.0 and 1.25 respectively). The mean blue:red ratio (0.86) was strongly affected by cloud cover. The light environment of shade habitats was also examined. Under cloudy conditions in an oak woodland, R:FR fell to ca. 0.55 during the leafy phase, but higher values (ca. 0.8) were recorded in late summer as a result of the seasonal trend in incident R:FR. Reflectance and transmittance spectra and pigment content of the leaves and the transmittance of the canopy were measured. Beneath a dense sugar beet canopy, R:FR was well-correlated with canopy transmittance and fell to very low levels (ca. 0.06). However, even this would not sustain a classical "high irradiance response", so it is unlikely to be important under natural conditions.